Motivasi Akademik dalam Self-compassion untuk Meminimalisir Perilaku Bullying - Hidajat, Helga Graciani; Pratiwi, Iqlima; Rahmi, Yaumul; Putri, Raissa Dwifandra (Universitas Negeri Malang, 2022)
Abstract: Bullying behavior still occurs in various parts of the world, including in Indonesia, until now. This bullying behavior had a negative impact, namely emotional and behavioral disturbances for both bullies and victims of bullying. The purpose of this research was to explore the factors that influence bullying behavior; psychological dynamics of perpetrators and victims of bullying as well as psychological dynamics of academic motivation development interventions in self-compassion in minimizing bullying behavior. This research is a literature study. The research procedure included reading theories related to academic motivation, self-compassion, academic motivation in self-compassion, bullying behavior, predictors of bullying, psychological dynamics of academic motivation in compassion in minimizing bullying. The results of this study were the factors that cause bullying behavior is a lack of moral knowledge about bullying behavior and its effects; parenting style that is too authoritarian and permissive; justification for bullying in schools. There were many negative impacts on bullying behavior, starting from emotional and behavioral disturbances in bullying perpetrators, which were related to aggression and emotional and behavioral disturbances in bullying related to low self-esteem, stress, depression, difficulty adapting, and even attempted suicide in victims of bullying. One of the interventions to minimize bullying behavior was by developing academic motivation in self-compassion to minimize bullying. Abstrak: Perilaku bullying masih terjadi di berbagai belahan dunia termasuk di Indonesia, hingga saat ini. Perilaku bullying ini memberi dampak yang negatif yakni gangguan emosi dan perilaku baik pada pelaku bullying maupun korban bullying. Tujuan penulisan artikel ini adalah melakukan studi literature terkait dengan faktor-faktor yang mempengaruhi perilaku bullying; dinamika psikologis pelaku dan korban bullying serta dinamika psikologis intervensi pengembangan motivasi akademik dalam self-compassion dalam meminimalisir perilaku bullying. Penelian ini merupakan penelitian studi literature. Prosedur penelitian ini meliputi membaca teori berkaitan dengan motivasi akademik, self-compassion, motivasi akademik dalam self-compassion, perilaku bullying, prediktor bullying, dinamika psikologis motivasi akademik dalam compassion dalam meminimalisir bullying. Hasil penelitian ini adalah Faktor-faktor yang menyebabkan perilaku bullying adalah kurangnya pengetahuan moral tentang perilaku bullying dan dampaknya; pola asuh orang tua yang terlalu otoriter dan permisif; pembenaran bullying di sekolah. Banyak dampak negatif dalam perilaku bullying mulai dari gangguan emosi dan perilaku pada pelaku bullying yakni berkaitan dengan agresi dan gangguan emosi dan perilaku pada bullying terkait dengan rendah diri, stress, depresi, susah beradaptasi, bahkan percobaan bunuh diri pada korban bullying. Salah satu intervensi untuk meminimalisir perilaku bullying dengan mengembangkan motivasi akademik dalam self-compassion untuk meminimalisir bullying.